Expression of Zymomonas mobilis adhB (encoding alcohol dehydrogenase II) and adhB-lacZ operon fusions in recombinant Z. mobilis. - Mackenzie, K F (1989)
The Zymomonas mobilis alcohol dehydrogenase II gene (adhB) was overexpressed 7- to 14-fold on a recombinant plasmid, accompanied by a small decrease in growth rate. A fragment containing the truncated gene with promoter reduced expression from the chromosomal gene as measured immunologically and enzymatically, consistent with the presence of a trans-active regulatory factor and positive regulatory control. Both the complete gene and the promoter fragment increased pyruvate decarboxylase and glucokinase activities, with no effect on alcohol dehydrogenase I or eight glycolytic enzymes. Tandem promoters from adhB expressed beta-galactosidase at higher levels than did either promoter alone in operon fusions. Addition of 50 microM zinc sulfate in minimal medium reduced the expression of adhB and of the operon fusions. Abundant but inactive alcohol dehydrogenase II was produced in iron-limited cells. This inactive enzyme did not form intracellular aggregates, and no morphological changes were apparent by transmission electron microscopy.